Seeing, Feeling, and Hearing the World. A Regenerative Worldview: Rinyi, Pirlirr and Liyan - Kankawa Nagarra [Olive] Knight; Anne Poelina; Sandra Wooltorton (Australian Journal of Environmental Education)
In this communication, the Australian authors – two Indigenous women and one woman with Anglo-Celtic ancestry – take us into Western Australian Indigenous language and worldviews, to help us reach toward a regenerative worldview. Indigenous words such as rinyi, pirlirr, and liyan are explored to point us in a direction unfamiliar to many English speakers, to Land and Country as living and responsive. The authors notice that it is very difficult to describe these terms in English, because English language does not seem sufficiently capacious to describe the depth of relational being-with Country that Indigenous languages portray. This may be changing, as various Indigenous and place-based groups publish their messages to the world. Within a methodology that is poetic and ontological, a storying method is used to illustrate elements of an Indigenous regenerative worldview that highlights the lyrics of life, for hope. It is for change agents who want to be transformative of the ways they participate with Country; and enable children to learn.